1989
DOI: 10.1093/brain/112.6.1445
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Amongst Chinese in Hong Kong

Abstract: A territory-wide investigation of southern Chinese patients with multiple sclerosis (MS) was conducted in Hong Kong. There were 47 patients, 35 of whom were clinically definite (CDMS), 6 laboratory-supported definite (LSDMS) and 6 clinically probable (CPMS). The prevalence rate was 0.88 per 10(5) population, which is of the same order as in other Oriental populations but much lower than in Caucasoid populations. Comparisons with major Oriental and Caucasian series showed essentially the same clinical picture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
1
34
1
3
Order By: Relevance
“…MS mortality was higher in whites than in other racial/ethnic groups, followed by Blacks, Hispanics, American Indians/Alaska Natives and Asians/Pacifi c Islanders. Previous studies have suggested that the prevalence of MS may be considerably lower in Hong Kong, Japan, Taiwan and India than it is in the US [31][32][33][34] . The MS mortality rate in Asians/Pacifi c Islanders was less than one tenth of the observed mortality rate in whites.…”
Section: Discussionmentioning
confidence: 99%
“…MS mortality was higher in whites than in other racial/ethnic groups, followed by Blacks, Hispanics, American Indians/Alaska Natives and Asians/Pacifi c Islanders. Previous studies have suggested that the prevalence of MS may be considerably lower in Hong Kong, Japan, Taiwan and India than it is in the US [31][32][33][34] . The MS mortality rate in Asians/Pacifi c Islanders was less than one tenth of the observed mortality rate in whites.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MS in Taiwan is lower than that of most Asian countries except China Shanghai [25] . An increase in prevalence with time is not only observed in Taiwan, but also in other Asian countries, including Japan, Hong Kong, Kuwait and Jordan [17,18,[26][27][28][29][30][31][32][33][34] . The ascertainment of MS has been greatly improved with the utility of magnetic resonance imaging, which has become more and more widely available in the recent 2 decades.…”
Section: Creutzfeldt-jakob Diseasementioning
confidence: 99%
“…Damit gehört Deutschland mit den skandinavischen Ländern, Schottland, Island, den USA, Kanada und Australien zu den Hochrisikogebieten weltweit (Prävalenzraten > 30/100.000) (Compston 1997). Die Prävalenz unter Schwarzafrikanern und Asiaten ist mit 5/100.000 dagegen gering (Kuroiwa Y 1982;Yu YL 1989;Miller DH 1990;Poser CM 1994). Einwanderer aus asiatischen Ländern in die USA oder nach Europa haben ein höheres Risiko zu erkranken als in ihrem Ursprungsland.…”
Section: Epidemiologie Der Msunclassified